2007
DOI: 10.1590/s0100-879x2006005000147
|View full text |Cite
|
Sign up to set email alerts
|

Roles of calcium and IP3 in impaired colon contractility of rats following multiple organ dysfunction syndrome

Abstract: The purpose of the present study was to explore changes in rat colon motility, and determine the roles of calcium and inositol (1,4,5)-triphosphate (IP 3 ) in colon dysmotility induced by multiple organ dysfunction syndrome (MODS) caused by bacteria peritonitis. The number of stools, the contractility of the muscle strips and the length of smooth muscle cells (SMC) in the colon, the concentration of calcium and IP 3 in SMC, and serum nitric oxide were measured. Number of stools, fecal weight, IP 3 concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In support of this hypothesis, several previous studies clearly showed that gut stasis leads to elevated gut permeability and bacterial translocation ( 75 , 84 87 ). This ultimately releases toxic mediators which further increases gut permeability ( 88 91 ). Conversely, alterations in the gut microbiota may to be involved in some neurological and autoimmune conditions ( 92 ), especially MS ( 93 ).…”
Section: Intestinal Calcium Absorption Gut Microbiota and Multiple mentioning
confidence: 99%
“…In support of this hypothesis, several previous studies clearly showed that gut stasis leads to elevated gut permeability and bacterial translocation ( 75 , 84 87 ). This ultimately releases toxic mediators which further increases gut permeability ( 88 91 ). Conversely, alterations in the gut microbiota may to be involved in some neurological and autoimmune conditions ( 92 ), especially MS ( 93 ).…”
Section: Intestinal Calcium Absorption Gut Microbiota and Multiple mentioning
confidence: 99%
“…The adequate relationship between GI physiology and overall homeostasis involves a variety of delicate functions; among these, the participation of gut motility, intestinal epithelial secretion and visceral perception mechanisms in association to systemic alterations have been somewhat explored (Duclos et al, 1991; Lackner et al, 2004; Zheyu et al, 2007; Yamamoto et al, 2008; Diebel et al, 2015; Yamamoto-Furusho et al, 2015). However, the contribution of other complex responses such as those regulated by the ENS or the intestinal epithelial barrier to the development of GI and extraintestinal disorders are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%